Albumin levels as a biomarker for second Intravenous Immunoglobulin (IVIG) treatment in Guillain-Barre syndrome (GBS). (April 2020) - Shalman, Anna; Savir, Shiri; Mechnik Steen, Yana; Ovanyan, Andrey; Boniel, Nancy; Koyfman, Leonid; Bichovsky, Yoav; Zlotnik, Alexander; Klein, Moti; Brotfain, Evgeni
Highlights: A 21-year-old male with GBS was treated successfully by 2 courses of IVIG. After second 5-day course of IVIG we recorded an increase in the patient's albumin level. Serum albumin levels may be considered a biomarker as part of the decision algorithm in GBS. Abstract: Background: Patients with GBS may develop hypoalbuminemia following treatment with Intravenous Immunoglobulin (IVIG), which is related to a poorer outcome. This report presents a patient with GBS and his clinical response to two courses of IVIG treatments in association with his albumin level. Case report: A previously healthy 21-year-old male was admitted to the GICU due to GBS with severity grade 5 (required assisted ventilation). IVIG treatment was initiated. Over the next two weeks there was no clinical improvement and Albumin level dropped from 4.5 gr/dL to a nadir of 2.3 gr/dL. A second course of IVIG was initiated. After initiation of the second course the patient's albumin began rising to 3.0 gr/dL and a clinical improvement followed this rise. Subsequently, he was weaned from mechanical ventilation within a few days. Conclusions: When considering a second course of IVIG treatment, serum albumin levels may be considered a biomarker as part of the decision algorithm.